Uji Mikrobiologi Air Perpipaan di Dusun Mundukkunci Desa Tegallinggah - Yuliasni Mardiyati (International Journal of Applied Chemistry Research, 2021)
This research is a descriptive study that aims to (1) determine the presence or absence of total coliform bacteria and fecal coliform in piped water in Dusun Mundukkunci, Tegallinggah Village, and (2) determine the quality of the piped water in terms of MPN values for total coliform and fecal coliform. The subject of this research is piped water in Dusun Mundukkunci, Tegallinggah Village, Sukasada District, and Buleleng Regency. The objective is to determine the microbiological quality of the piped water in terms of the total coliform MPN and fecal coliform values. The determination of the sample is done by random sampling an area based on consideration of the distance of the spring from the distribution channel in people's homes. The presence of total coliform bacteria and fecal coliform in piped water samples was tested using the double tube method. The results showed that (1) the piped water in Dusun Mundukkunci, Tegallinggah Village, contains total coliform bacteria and fecal coliform, and (2) the microbiological quality of the piped water is suitable for use as a source of clean water, but it is not suitable for direct drinking water because of its The MPN for springs and storage tanks exceeds the standards set by the government. In its utilization, the water needs to be treated first, for example by adding a disinfectant to the holding tank or by boiling it to kill the bacteria in the water.